2019
DOI: 10.1021/acsami.8b18307
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of the Interface between Hybrid Organic–Inorganic Perovskite and Atomic Layer Deposited Al2O3

Abstract: Ultrathin metal oxides prepared by atomic layer deposition (ALD) have gained utmost attention as moisture and thermal stress barrier layers in perovskite solar cells (PSCs). We have recently shown that 10 cycles of ALD Al2O3 deposited directly on top of the CH3NH3PbI3–xClx perovskite material, are effective in delivering a superior PSC performance with 18% efficiency (compared to 15% of the Al2O3-free cell) with a long-term humidity-stability of more than 60 days. Motivated by these results, the present contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 66 publications
2
42
0
Order By: Relevance
“…Several studies have reported that excessive exposure to metal-organic ALD precursors can damage the perovskite material by etching away organic cations from the perovskite surface. [55][56][57][58] We used the same analysis to investigate the nucleation of ALD SnO 2 on C 60 that has been coated with a thin layer of PEIE. The thickness of the PEIE layer is approximately 2 nm as measured by spectroscopic ellipsometry and can be controlled by varying the concentration of the PEIE solution ( Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that excessive exposure to metal-organic ALD precursors can damage the perovskite material by etching away organic cations from the perovskite surface. [55][56][57][58] We used the same analysis to investigate the nucleation of ALD SnO 2 on C 60 that has been coated with a thin layer of PEIE. The thickness of the PEIE layer is approximately 2 nm as measured by spectroscopic ellipsometry and can be controlled by varying the concentration of the PEIE solution ( Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Insulting ALD-Al 2 O 3 has been demonstrated to be efficient barriers. [179][180][181][182][183] For example, Koushik et al deposited an ultra-thin (≈2 nm) Al 2 O 3 layer on top of the MAPbI 3−x Cl x perovskite using the ALD method to enhance the resistance of PSC to moisture (Figure 7f). It should be noted that this moisture barrier is required to be thin enough to allow the tunneling of carriers.…”
Section: Inorganic Barriers Between Perovskite and Ctlsmentioning
confidence: 99%
“…Based on previous reports, each pulse step (the metal precursor and the co-reactant) influences the perovskite active layer in somewhat contradicting ways. While a study reported to not observe any degradation of the perovskite after exposure of repeated pulses of TMA and H 2 O at 80 °C, several studies reported the loss of nitrogen, implying etching of MA + from the perovskite active layer [ 55 ]. A study found that TMA partial pressures of 0.1 Torr can etch MAPbI 3 at 75 °C, and observed continual mass loss of perovskite at high TMA exposures of 3 Torr at 25 °C [ 56 ], suggesting that variations in ALD process parameters result in very different perovskite surfaces, which may explain the discrepancies in literature.…”
Section: Ald Above the Perovskite Layermentioning
confidence: 99%
“…Several reports demonstrated successful encapsulation of PSC devices by ALD single materials or nanolaminates of multiple stacks of alternating materials by ALD and/or organic materials. For example, encapsulated semitransparent PSC devices with a bilayer of 50-nm Al 2 O 3 -coated polyethylene terephthalate (PET) resulted in stable devices based on storage in ambient air for over 45 days [ 55 ].…”
Section: Ald Above the Perovskite Layermentioning
confidence: 99%